Diabetes self‐care behaviors in adults with disabilities: A systematic review. Issue 2 (5th November 2019) - Yang, Eunjin; Kim, Hee Jung; Ryu, Hyunju; Chang, Sun Ju
Abstract: Aim: The integrated evidence on diabetes self‐care behaviors in people with a disability is not commensurate with the growing number of people with both diabetes and a disability. This study aims to identify factors influencing self‐care behaviors in adults with diabetes and a disability based on a thorough review of the current evidence. Methods: This review followed the Cochrane guidelines for systematic review research and complies with the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis. To find eligible articles, five electronic databases—PubMed, Embase, CINAHL, Psych‐articles, and the Cochrane Library—were searched, from the beginning of the chronological period covered by each database to June 2017. Four researchers independently conducted study selections, extracted data, and assessed the data quality. Results: Twenty studies were reviewed to identify barriers to and facilitators of diabetes self‐care behaviors. For people with developmental disabilities, the most prominent facilitator of self‐care behaviors was the support they received for the behaviors. For people with visual impairments, that facilitator was the use of helpful assistive devices that take advantage of another sense. The main barriers to self‐care behaviors were mobility limitation for people with physical disabilities and lack of accessibility for people with visual impairments. Conclusions: This review has identified barriers to and facilitators of diabetes self‐care behaviors by type of disability. Healthcare services need to be tailored to these facilitators and barriers, and differentiated by type of disability.